TAX FRAUD AND WELFARE EFFECTS IN NIGERIA: AN ARDL ESTIMATION (American Journal of Business Management, Economics and Banking, 2026)
This study investigates the impact of tax fraud on welfare outcomes in Nigeria, focusing on Personal Property Tax Fraud and Corporate Income Tax Fraud as key determinants of human development. Recognizing that tax revenue constitutes a critical source of funding for public services, the research explores how fraudulent practices erode fiscal capacity and constrain social welfare, measured through the Human Development Index. Employing an ex-post facto research design, the study utilises secondary data spanning 1999 to 2023, sourced from the Nigerian Revenue Service Tax ProMax database and supplemented with estimates derived from the Corruption Perceptions Index. The methodological framework integrates a stationarity test using the Augmented Dickey–Fuller approach, lag length selection criteria, Auto Regressive Distributed Lag estimation, Bounds Cointegration Test, and long-run Auto Regressive Distributed Lag modelling to capture both short-term and long-term dynamics. The results indicate that while PPTF is stationary at level, Human Development Index and Corporate Income Tax Fraud are stationary at first difference, validating the suitability of the Auto Regressive Distributed Lag framework. Empirical findings reveal that both Personal Property Tax Fraud and Corporate Income Tax Fraud exert significant and negative effects on Human Development Index, confirming that tax fraud diminishes government capacity to finance welfare-enhancing programs and undermines human development. The study concludes that combating tax fraud through stronger enforcement, institutional reforms, and public awareness initiatives is essential for improving welfare outcomes in Nigeria. These findings provide critical policy insights for fiscal authorities and underscore the importance of effective tax administration in promoting sustainable development.